EXPRESSION OF SYNONYMOUS LEXEMES IN HAYDAR KHOREZMI'S "GULSHAN UL-ASROR" MASNAVI - Tashmatova Nilufar Choriyevna (Web of Journals Publishing, 2025)
In this article, the synonyms expressed in the masnavi "Gulshan ul-asrar" by Heydar Khorazmi, one of the mature representatives of our classical literature, who lived and created in Khorezm in the late XIV and early XV centuries, are classified and analyzed. In the work, the synonymy between the words belonging to the same category is fruitful among the words belonging to the noun category. When describing the synonyms expressed in Masnavi according to their genetic characteristics, synonymy is actively performed between words belonging to the same language, that is, Turkish words.
Keywords: Turkish word, word group, synonym, possessive word, lexeme, masnavi, noun, verb.